2016
DOI: 10.1590/1983-21252016v29n222rc
|View full text |Cite
|
Sign up to set email alerts
|

PROPAGATION OF ANTIMICROBIAL RESISTANT Salmonella spp. IN BIVALVE MOLLUSKS FROM ESTUARY AREAS OF BAHIA, BRAZIL

Abstract: -In recent years, the emergence of resistant pathogens has complicated the treatment of bacterial infections in livestock production as well as in the medical field, due to the development of resistance mechanisms by microorganisms. The objective of this study was to delineate the antimicrobial resistance profile of Salmonella spp. strains isolated from bivalve mollusks (oysters and mussels) and from estuarine environment water of two regions of Bahia, Brazil. Twenty-seven strains, 12 isolated from bivalve mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
2
5
1
1
Order By: Relevance
“…As expected, the occurrence of resistant Salmonella strains isolated from molluscan shellfish was significantly lower compared with the occurrence reported for poultry, pork, and bovine. However, the level of resistance reported in the present work was higher than that reported by [ 20 ]. Molluscan shellfish are filter-feeding animals, and the presence of resistant Salmonella serovars in them may indicate an alteration of water ecosystems by human action [ 21 ].…”
Section: Discussioncontrasting
confidence: 89%
“…As expected, the occurrence of resistant Salmonella strains isolated from molluscan shellfish was significantly lower compared with the occurrence reported for poultry, pork, and bovine. However, the level of resistance reported in the present work was higher than that reported by [ 20 ]. Molluscan shellfish are filter-feeding animals, and the presence of resistant Salmonella serovars in them may indicate an alteration of water ecosystems by human action [ 21 ].…”
Section: Discussioncontrasting
confidence: 89%
“…Observou-se que a quantidade de CT na água do cultivo oscilou de < 2 até > 1.600 NMP/100 mL, já o Ctt variou de < 2 até 375 NMP/100 mL, ambos os grupos com os maiores níveis no mês de janeiro, conforme apresentado na (Tabela 1). SILVEIRA et al, 2016).…”
Section: Resultsunclassified
“…Furthermore, our detected biomarkers for increased Phd-Doc toxin-antitoxin genes, are attributed with biochemical processes including antibiotic resistance [274]. One explanation for these findings may be related to mussels hosting antibiotic resistant symbionts [275,276], multidrug-resistant pathogens, [277], and enhanced horizontal gene transfer within their gut microbial community [278]. Previous research has also shown that mussels bioaccumulate various metals [279,280], including elements found in this biomarker study, copper and zinc [281].…”
Section: N Impacted the Genomic Potential Of Comammox Nitrospirasupporting
confidence: 59%